2021
DOI: 10.3389/fimmu.2021.620284
|View full text |Cite
|
Sign up to set email alerts
|

Resident Innate Immune Cells in the Cornea

Abstract: The cornea is a special interface between the internal ocular tissue and the external environment that provides a powerful chemical, physical, and biological barrier against the invasion of harmful substances and pathogenic microbes. This protective effect is determined by the unique anatomical structure and cellular composition of the cornea, especially its locally resident innate immune cells, such as Langerhans cells (LCs), mast cells (MCs), macrophages, γδ T lymphocytes, and innate lymphoid cells. Recent s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0
6

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 125 publications
(175 reference statements)
1
52
0
6
Order By: Relevance
“…Neutrophils and γδ-T cells are the essential innate immune cells on the ocular surface of mice and play an important role in maintaining the healthy state of ocular surface and pathological reaction. 57 59 However, it is not clear whether HFI alters the diurnal trafficking of neutrophils and γδ-T cells to the cornea. In the corneas of NC mice collected at hourly intervals, the active trafficking of neutrophils and γδ-T cells to the corneal limbal region occurred during the dark cycle and peaked at ZT18 ( Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Neutrophils and γδ-T cells are the essential innate immune cells on the ocular surface of mice and play an important role in maintaining the healthy state of ocular surface and pathological reaction. 57 59 However, it is not clear whether HFI alters the diurnal trafficking of neutrophils and γδ-T cells to the cornea. In the corneas of NC mice collected at hourly intervals, the active trafficking of neutrophils and γδ-T cells to the corneal limbal region occurred during the dark cycle and peaked at ZT18 ( Figs.…”
Section: Resultsmentioning
confidence: 99%
“…We examined corneal metrics at one time point after abrasion and resveratrol treatment, but it is possible that macrophage infiltration and resveratrol's effects on macrophages are more pronounced at earlier time points. We did not 20 differentiate between M1-and M2-type macrophages, which are thought to be involved in the initiation and inhibition of inflammatory processes, respectively (Liu J. and Li, 2021). A previous study using a myocardial infarction mouse model found that daily oral resveratrol promoted the proliferation of macrophages in the area surrounding that cardiac infarct and their polarization to M2-type macrophages (Liu S. et al, 2019).…”
Section: Discussionmentioning
confidence: 75%
“…Mast cells are present in the cornea, conjunctiva, limbus, choroid, iris, optic nerve and its meninges, as well as in limited numbers in the cornea. They release various multifunctional pro- and anti- inflammatory cytokines, chemokines, and growth factors [ 75 , 76 , 77 , 78 , 79 ]. Additionally, they are present in the corneoscleral, precorneal limbus region that is highly innervated and vascularized, and houses stem cells [ 80 ].…”
Section: Mast Cells In Wound Healing and Fibrosismentioning
confidence: 99%